1983
DOI: 10.1111/j.1540-4560.1983.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Social Context as Determinants of Black Women's Resistance to Challenges

Abstract: In the past, social psychological researchers have generally treated sex and race as independent status characteristics. The utility of this unidimensional model is questioned. Literature examining sex and race differences in status which then predict behavior (specifically resistance to influence) is reviewed to demonstrate the inadequacy of separating the effects of these characteristics. The importance of sex and race as both personal and contextual characteristics is then discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Reinforcing this view, the federal government has removed its backing from many of the civil rights laws passed in the 1960s and 1970s that gave women and other minority groups a chance for full participation in American society in general, and higher education specifically (Washington & Harvey, 1989). Even still, Adams (1983) contended that "such legal reforms did not guarantee change in discriminatory attitudes and behaviors. Both women and blacks [sic] continue to be underemployed and underpaid" (p. 69).…”
Section: Overview Of African American Women Compared To Other Membersmentioning
confidence: 97%
“…Reinforcing this view, the federal government has removed its backing from many of the civil rights laws passed in the 1960s and 1970s that gave women and other minority groups a chance for full participation in American society in general, and higher education specifically (Washington & Harvey, 1989). Even still, Adams (1983) contended that "such legal reforms did not guarantee change in discriminatory attitudes and behaviors. Both women and blacks [sic] continue to be underemployed and underpaid" (p. 69).…”
Section: Overview Of African American Women Compared To Other Membersmentioning
confidence: 97%
“…These results were consistent with other results in the literature. For example, in a study of biracial groups, Adams (1983) found that African American women were more readily accepted in roles of influence than African American men. She argued that White society has historically allowed more assertive behavior from African American women than African American men because females of any race are regarded as less dangerous than males.…”
Section: Influence Of Applicant Race and Gendermentioning
confidence: 99%
“…If personal comfort is a criterion for advancement, then black females will be promoted faster and progress higher in the corporate hierarchy than their black male counterparts. Adams' (1983) study of biracial, cross-gender social encounters concludes that white men perceive black women neither in the same sexual role as white women nor in the same racial role as black men.…”
Section: Black Females and Black Malesmentioning
confidence: 99%
“…Progression upwards in the organisation has historically been easier for men. Behaviour is also associated with race (Adams, 1983). Whites often view blacks as angry, lacking motivation and unwilling to conform to social (white) norms, while perceiving themselves more positively.…”
Section: Black Females and Black Malesmentioning
confidence: 99%